Projeto de uma bancada de aspersão de fluidos supressores de poeira - SOUZA, Gustavo Braga de (2024)
The suppressantr spray bench proposes standardization and quality control in the spraying process of aqueous solutions used in the laboratory for tests and experiments of dust suppressant compositions applied to the mining industry. The present work is in search of a bench projection that will be of great use for the Fluid Dynamics and Particulates Laboratory of the Federal University of Pará on the Tucuruí campus. The projection seeks to approximate a small-scale sprinkle model to a real sprinkle model of suppressor fluids in ore wagons used in industry, locating the necessary project equipment seeking the best cost-benefit ratio and reuse of tools and equipment available to meet pre- -project requirements. The new consolidated sprinkle method is yet another advance in the improvement of dust control case studies that is already under development. Although developed with a focus on testing polymeric fluids in ore piles and wagons, it can still meet several other spraying demands that may arise in this field of research. From the project developed, it will be possible to build the equipment and obtain control over the amount of suppressor mass sprayed during the process, standardize the spraying process to be replicated in several and generate more consistent results for studies that depend on this spraying procedure.